The journey of language acquisition of third culture kids living in Indonesia - Solange Francielle Silva; Soni Mirizon; Sary Silvhiany (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
International mobility is a distinctive feature of the world of the 21st century. Individuals and their families are often moving due to business, job assignments, pursue further education etc. The children brought up in this mobility scenario are known as Third Culture Kids (TCKs). They are often exposed to different languages and cultures, what gives them unique abilities, but also brings numerous challenges. The objective of this article was to have a better understanding of TCKs living in Indonesia and what their journey of language acquisition in the country looked like. To answer these questions we collected data from 2 TCKs living in Indonesia, through interviews and artefacts using thematic analysis. The findings revealed that the TCKs living in Indonesia are traditional TCKs according to Pollock & Recken’s framework of TCKs. Regarding to their journey of language acquisition the parents played an important role choosing schools and implementing a family language policies at home in order to teach them their first language, hence, parents language. However the TCKs chose to use English, as their first language due to the third culture environment they were surrounded with.